Review of the impacts of COVID-19 pandemic on the employment of college graduates in China and countermeasures to it - Wang, Huicui; Wang, Chun (Frontiers in Public Health, 2024)
The employment of college graduates has always been the focus issue of the whole society. Affected by the COVID-19, college graduates are facing a severe employment situation. In the present study, we explore the impacts of the COVID-19 on the employment of college graduates. We explore the employment promotion measures introduced by Chinese government and colleges and universities through a quick review and illustrate the difficulties that college graduates face. Furthermore, the present study explores the impacts of the COVID-19 on five aspects of the employment of college graduates: recruitment demand reduce, employment competition rise, employment channels change, psychological anxiety increase and employment structural contradiction intensify. In addition, we conclude that the employment promotion measures introduced by Chinese government and colleges and universities in respond to the impacts of the COVID-19 on the employment of college graduates have significantly promoted the employment of college graduates to a large extent and we provide implications based on the application of the study. The findings of the present study are of great significance for all countries worldwide to better cope with various similar emergency events, to alleviate employment pressure and to promote better and fuller employment of college graduates.